2014
DOI: 10.2147/oarrr.s53757
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective analysis of treatment modalities in diabetic muscle infarction

Abstract: BackgroundDiabetic muscle infarction (DMI) is a spontaneous necrosis of skeletal muscle of unknown etiology. The major risk factor is longstanding uncontrolled diabetes mellitus (DM). Optimal treatment for DMI is not known. The purpose of this study was to analyze the outcome of surgical treatment, physiotherapy, and bed rest in DMI.MethodsWe searched Medline from its inception to April 2013. We selected cases that provided sufficient data on recovery duration, recurrences, and non-recurrences. Baseline charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…Some authors have recommended avoidance of PT because of prolonged recovery time 63 while others have not observed this in their study populations. 98 99 In this review, patients receiving PT had the longest mean time to symptom resolution at 76.5 days. Recovery times for other treatment modalities were 41.7 days for patients receiving bed rest, and 28.5 days with supportive care/bed rest plus a non-steroidal anti-inflammatory drug (NSAID).…”
Section: Managementmentioning
confidence: 85%
“…Some authors have recommended avoidance of PT because of prolonged recovery time 63 while others have not observed this in their study populations. 98 99 In this review, patients receiving PT had the longest mean time to symptom resolution at 76.5 days. Recovery times for other treatment modalities were 41.7 days for patients receiving bed rest, and 28.5 days with supportive care/bed rest plus a non-steroidal anti-inflammatory drug (NSAID).…”
Section: Managementmentioning
confidence: 85%
“…2 The recurrence rate of DMI is found to be lowest with bed rest followed by physiotherapy and was highest in those who underwent surgery. 10 Patients with DMI are at high risk of recurrence, which is reported to be from 34.9% to 45.0% in different studies, and in about two-thirds of patients these recurrences are noted in a different location or muscle group than in the initial presentation. 2,3 Our patient had recurrence of DMI after three years with current involvement of multiple muscle groups.…”
Section: Discussionmentioning
confidence: 97%
“…Onyenemezu and Capitle compared surgery, physiotherapy and bed rest in the treatment of DMI and found that the patients undergoing surgery (muscle excision biopsy ) had signifi cantly prolonged symptom recovery time when compared to those managed by physiotherapy or bed rest. 10 Horton et al also showed that time to recovery was numerically lower in patients who received supportive care (glycaemic control and pain management/best rest) plus a nonsteroidal anti-infl ammatory drug, than those who were managed only by bed rest. 2 The recurrence rate of DMI is found to be lowest with bed rest followed by physiotherapy and was highest in those who underwent surgery.…”
Section: Discussionmentioning
confidence: 99%
“…It should be reserved for atypical clinical presentations when the standard investigation methods require further confirmation. Even though the needle/incision biopsy has been advocated instead of the excision biopsy, it is not as well tolerated by the patient [ 13 ].…”
Section: Discussionmentioning
confidence: 99%